How can we promote gender and sex equality in orthopaedics and traumatology surgery? Research avenues perspectives - Agathe Yvinou; Romain Alain (Journal of Orthopaedic Surgery and Research)
Abstract Gender and sex disparities persist in orthopaedic and traumatology surgery, making it one of the least diverse medical specialties worldwide. Despite growing women representation in medical education, women continue to be significantly underrepresented in orthopaedics, occupying only 6–8% of surgical roles. This underrepresentation extends to academic leadership, research, and public speaking opportunities, ultimately limiting innovation and the quality of patient care. Systemic barriers—such as gender bias, lack of mentorship, and misperceptions about physical demands—discourage women from entering and advancing in the field. This manuscript explores the current landscape of gender inequality in orthopaedics and identifies strategic interventions to promote equity. Solutions include enhancing recruitment through early exposure, fostering inclusive institutional cultures, expanding mentorship and sponsorship opportunities, and implementing supportive policies for work-life integration. In patient care, disparities in diagnosis, pain management, surgical decision-making, and rehabilitation access disproportionately impact women. We advocate for the development of gender-inclusive clinical guidelines, equitable research funding, and standardized assessment tools. Additionally, the role of public awareness is examined, emphasizing the need to highlight success stories, engage male allies, and conduct outreach through educational and community initiatives. Programs such as the Perry Initiative, Nth Dimensions, and campaigns like HeForShe are shown to play pivotal roles in shifting perceptions and increasing diversity. Addressing these disparities is not only a matter of justice but also essential to achieving excellence in clinical outcomes. This article offers a comprehensive framework for fostering gender and sex equality in orthopaedic and traumatology surgery through systemic, cultural, and policy-level change.